2015
DOI: 10.1007/s12031-015-0489-6
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Significance of the Plasma Let-7 Family in Anti-N-methyl-d-aspartate Receptor Encephalitis

Abstract: The study aimed to investigate the expression and significance of the plasma let-7 family in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Blood samples from 5 anti-NMDAR encephalitis patients and 5 negative controls were collected for microarray analysis. Blood samples from10 anti-NMDAR encephalitis patients, 10 anti-NMDAR encephalitis patients whose physical conditions have improved after 3 months of immunotherapy, 20 virus (meningitis) encephalitis patients, 20 tuberculosis (meningitis) encephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In MS, it has been demonstrated that there is a significant increase in the number of CD19 + cells in the blood 36 . Therefore, it would be of interest to perform cell type-specific studies to validate miR-345 as a biomarker for the diagnosis and prognosis of MS. Two recent studies did not observe different let-7b levels between individuals with MS and HCs 37 38 . This miRNA has however been linked to neurodegeneration; elevated amounts of let-7b were found in the cerebrospinal fluid (CSF) of patients with Alzheimer’s disease 39 .…”
Section: Discussionmentioning
confidence: 80%
“…In MS, it has been demonstrated that there is a significant increase in the number of CD19 + cells in the blood 36 . Therefore, it would be of interest to perform cell type-specific studies to validate miR-345 as a biomarker for the diagnosis and prognosis of MS. Two recent studies did not observe different let-7b levels between individuals with MS and HCs 37 38 . This miRNA has however been linked to neurodegeneration; elevated amounts of let-7b were found in the cerebrospinal fluid (CSF) of patients with Alzheimer’s disease 39 .…”
Section: Discussionmentioning
confidence: 80%
“…For Japanese encephalitis virus (JEV), miR-19b-3p and miR-155 were shown in regulating the JEV-induced inflammatory response [ 25 , 26 ]; miR-146a suppresses the cellular immune response in human microglial cells during JEV infection [ 27 ], and miR-33a-5p contributes to viral replication by targeting eukaryotic translation elongation factor 1A1 during JEV infection [ 30 ]. For the miRNAs associated with anti-NMDA receptor encephalitis, the let-7 family has been discovered in the literature, and the expression levels of let-7a, let-7b, let-7d, and let-7f were shown to be significantly downregulated in anti-NMDAR encephalitis compared with the negative controls [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The let-7 family was reported to be related to anti-NMDA receptor encephalitis [ 2 , 28 ]. let-7f is the only common miRNA of vaccine and anti-NMDA receptor encephalitis from Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are also related to the development of Parkinson’s disease (PD) [ 49 , 50 ], frontotemporal dementia [ 51 ], Alzheimer’s disease [ 52 ], and spinal muscular atrophy [ 53 ]. Additionally, let-7b is a miRNA biomarker for anti-NMDA receptor encephalitis [ 54 , 55 , 56 ]. In addition to being a useful disease biomarker, miRNA can be used to explore the association between two diseases or between disease and vaccination.…”
Section: Micrornamentioning
confidence: 99%
“…Overexpression of miR-378-5p was found to induce cell cycle arrest and promote apoptosis in CRC cells. In addition, miR-378-5p was shown to down-regulate gene BRAF in CRC cells [ 54 ]. Ectopic expression of miR-18a was found to inhibit the repair of DNA damage induced by etoposide, leading to the accumulation of DNA damage and increasing colon cancer cell apoptosis [ 70 ].…”
Section: Mirna In Apoptosis Of Colorectal Cancermentioning
confidence: 99%